Five nights at freddy's eaudiobook The official movie novel. - Cawthon, Scott (Five Nights at Freddy's., 2023)
The official movie novelization audiobook of the Five Nights at Freddy's movie! The hugely anticipated Five Nights at Freddy's movie from director Emma Tammi starring Matthew Lillard (Scream, Scooby-Doo) and Josh Hutcherson (The Hunger Games series, The Disaster Artist) hits theaters on October 27th, 2023, with a script from creator Scott Cawthon, Seth Cuddeback, and Emma Tammi. This movie novelization audiobook is a must-have for any Freddy fan!